Power by Deception: Mamet’s Matters of Confidence - Collard, Christophe (Pivot: A Journal of Interdisciplinary Studies and Thought, 2011)
This essay addresses David Mamet’s ambivalent attitude towards deception along the cases of his play The Shawl (1985) and his film House of Games (1987) – two works revolving round and structured as a con game. Based on the reasoning that the con man, like the dramatist, capitalizes on language’s power to connect and confuse, my argument seeks to establish dramatic deception as an engine of reflection. Moreover, given Mamet’s idiosyncratic, almost didactic rejection of a clear, agonistic division between winner and loser, true and false, good and evil, the concept of deceit itself can be tentatively repurposed from pejorative product to productive process by shifting focus from morality to machination. Ultimately, this should produce a frame of assent capable of integrating diversity, processing morality, and stimulating reflexivity.